Analisis Struktur Pasar, Perilaku Perusahaan, dan Kinerja Perusahaan dalam Industri Telekomunikasi Indonesia - Gading Nugroho; - Darwanto (MediaTrend, 2020)
The number of Indonesian telecommunications users has always increased from year to year. However, the performance of most telecommunications companies suffered losses. The market structure of Indonesian telecommunications industry that tends to be concentrated is thought to have an influence on the performance of companies in this industry. This study uses a structure, conduct, and performance (SCP) paradigm to analyze the Indonesian telecommunications industry for the period 2011Q1 to 2019Q2. The purpose of this study is to examine the SCP theory in explaining the relationship between market structure and performance of the Indonesian telecommunications industry for the period 2011Q1 to 2019Q2. Panel data is used in this study to see the effect of Market Share (MS), Advertising to Sales Ratio (ADV), and X-efficiency (XEFF) on Return on Asset (ROA). The results of panel data analysis using Fixed Effect Model (FEM) showed that the Advertising to Sales Ratio (ADV) variable had a significant negative effect on return on asset (ROA). While Market Share (MS) and X-efficiency (XEFF) do not have a significant effect on Return on Asset (ROA). SCP theory hypotesis is not proven in the Indonesian telecommunications industry.